Liver volume is a prognostic indicator for clinical outcome of patients with alcoholic hepatitis. - Breguet, Romain; Ronot, Maxime; Goossens, Nicolas; Hansen, Catrina; Giostra, Emiliano; Majno, Pietro; Becker, Christoph; Spahr, Laurent; Terraz, Sylvain (Abdominal Radiology, 2017)
Purpose: To evaluate the prognostic value of abdominal computed tomography (CT) in patients with alcoholic hepatitis (AH). Methods: This ancillary study was based on data collected during a previous randomized controlled trial in patients with AH. Clinical response was defined as the improvement of the baseline MELD score ≥3 points at 3 months. All patients underwent contrast-enhanced CT of the abdomen. The following parameters were measured: (1) liver density, spleen density, and liver-to-spleen density ratio; (2) liver-to-body weight (LBW) ratio; and (3) subcutaneous fat, visceral fat, and muscular content. Improvers and non-improvers were compared with univariate, multivariate, and ROC analyses. Results were compared with a validation cohort of patients. Results: Fifty-eight patients (mean age, 56 years) were analyzed, including 34 (59 %) improvers. On multivariate analysis, LBW ratio (OR = 3.73; 95 % CI, 1.65-8.46; p = 0.002) and subcutaneous fat (OR = 1.01; 95 % CI, 1.00-1.02; p = 0.022) were associated with clinical response, with AUROC curves of 0.78 ± 0.06 ( p < 0.001) and 0.66 ± 0.07 ( p = 0.043), respectively. LBW ≥2.4 % predicted response with 88 % sensitivity and 63 % specificity. In the validation cohort ( n = 42, 64 % improvers), the same cut-off value predicted response with 93 % sensitivity and 60 % specificity. Conclusions: In patients suffering from AH, the liver volume appears to be a major positive prognostic factor.